Self‐Healing and Stretchable 3D‐Printed Organic Thermoelectrics. (21st October 2019) - Kee, Seyoung; Haque, Md Azimul; Corzo, Daniel; Alshareef, Husam N.; Baran, Derya
Abstract: With the advent of flexible and wearable electronics and sensors, there is an urgent need to develop energy‐harvesting solutions that are compatible with such wearables. However, many of the proposed energy‐harvesting solutions lack the necessary mechanical properties, which make them susceptible to damage by repetitive and continuous mechanical stresses, leading to serious degradation in device performance. Developing new energy materials that possess high deformability and self‐healability is essential to realize self‐powered devices. Herein, a thermoelectric ternary composite is demonstrated that possesses both self‐healing and stretchable properties produced via 3D‐printing method. The ternary composite films provide stable thermoelectric performance during viscoelastic deformation, up to 35% tensile strain. Importantly, after being completely severed by cutting, the composite films autonomously recover their thermoelectric properties with a rapid response time of around one second. Using this self‐healable and solution‐processable composite, 3D‐printed thermoelectric generators are fabricated, which retain above 85% of their initial power output, even after repetitive cutting and self‐healing. This approach represents a significant step in achieving damage‐free and truly wearable 3D‐printed organic thermoelectrics. Abstract : Self‐healing and stretchable 3D‐printed organic thermoelectrics are developed using a viscoelastic ternary composite, which provides stable thermoelectric performance up to 35% tensile strain and autonomously recovers its thermoelectric properties after being severed by cutting. Using this self‐healable and solution‐processable composite, 3D‐printed thermoelectric generators are fabricated, which retain above 85% of their initial power output, even after repetitive cutting and self‐healing.